Effect of increased cage length on locomotor activity of juvenile blue foxes (Alopex lagopus) - Korhonen, Hannu T.; Jauhiainen, Lauri; Niemelä, Paavo (International Fur Animal Scientific Association (IFASA), 1998)
V ok